1987
DOI: 10.1128/jb.169.1.260-271.1987
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of nitrogen-regulatory (ntr-like) mutations in Rhodobacter capsulatus by an Escherichia coli gene: cloning and sequencing of the gene and characterization of the gene product

Abstract: In vivo genetic engineering by R' plasmid formation was used to isolate an Escherichia coli gene that restored the Ntr+ phenotype to Ntr- mutants of the photosynthetic bacterium Rhodobacter capsulatus (formerly Rhodopseudomonas capsulata; J. F. Imhoff, H. G. Trüper, and N. Pfenning, Int. J. Syst. Bacteriol. 34:340-343, 1984). Nucleotide sequencing of the gene revealed no homology to the ntr genes of Klebsiella pneumoniae. Furthermore, hybridization experiments between the cloned gene and different F' plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 77 publications
1
34
0
Order By: Relevance
“…The gene efg (nadE) was found to code for an ammonium-dependent NAD synthetase (64). Purified NAD synthetase is homodimer with a subunit molecular mass of 30.6 kDa (65). There is strong evidence that ammonium is the sole physiological donor of the amino group for NadE in E. coli and S. Typhimurium (64,66,67), which is in contrast to the eukaryotic enzymes, which are glutamine dependent.…”
Section: Other Enzymes Capable Of Direct Ammonium Assimilationmentioning
confidence: 95%
See 1 more Smart Citation
“…The gene efg (nadE) was found to code for an ammonium-dependent NAD synthetase (64). Purified NAD synthetase is homodimer with a subunit molecular mass of 30.6 kDa (65). There is strong evidence that ammonium is the sole physiological donor of the amino group for NadE in E. coli and S. Typhimurium (64,66,67), which is in contrast to the eukaryotic enzymes, which are glutamine dependent.…”
Section: Other Enzymes Capable Of Direct Ammonium Assimilationmentioning
confidence: 95%
“…With the vesicles, binding of glutamine was insensitive to variations in ionic strength and pH (22,65,154,327) and required neither potassium nor phosphate ions, whereas glutamine transport activity was inhibited by increasing ionic strength, had a narrow pH optimum, and required potassium and phosphate ions (328). Glutamine uptake into cells was inhibited by osmotic stress produced by NaCl but was stimulated when sucrose was used instead (329).…”
Section: Glutamine Transportermentioning
confidence: 95%
“…The R . capsulatus mutants RC27, RC28, RC29 and RC34, derived from the wild-type strain B10, showed similar growth properties, except that growth on glutamine was very slow (Willison et al, 1985;Allibert et al, 1987). Strain B10 is unable to utilize NO, as sole nitrogen source, so no conclusion can be drawn from these mutants as to the effects of adgA mutations on NO, assimilation in R .…”
Section: Growth Characteristicsmentioning
confidence: 90%
“…pneumoniae. An E. coli gene which complements the 'Ntr-like' mutants of R. capsulatus has been isolated (Allibert et al, 1987) and nucleotide sequencing of the gene has shown it to be unrelated to the known ntr genes of E. coli. The approximate map position of the gene (34-39 min) was determined, and no gene involved in nitrogen metabolism has so far been mapped to this region.…”
Section: Introductionmentioning
confidence: 99%
“…It may be relevant that the E. coli protein homologous to OutB has been shown to be a dimer of M,. 60000 (Allibert et al, 1987).…”
Section: The Wild-type Allele Is Donzinantmentioning
confidence: 99%